Intermittent ice-cooling to prevent skin heat injury caused by high-intensity focused ultrasound therapy targeting desmoid-type fibromatosis: A case report - Liangyu Fang; Xiaoye Hu; Yinchuan Xu; Hongling Sun; Hong Shen (Elsevier, 2021)
Introduction: Desmoid-type fibromatosis (DF) is a fibrous tumor characterized by low-grade malignant and easy invasive growth and high recurrence. High-intensity focused ultrasound (HIFU) therapy has been identified as a novel non-invasive approach for DF treatment; however, the ultrasonic energy generated by HIFU can cause skin heat injury. Case: A 31-year-old female patient with signs and symptoms of DF received treatment in our institution. The patient had undergone HIFU treatment six times from April 27, 2018, to August 21, 2019. After HIFU therapy for the third time, she had a third-degree skin burn showing as orange peel-like change and spent three months to promote the recovery of the skin lesions. An intermittent ice-cooling strategy was used to avoid skin damage during the fourth HIFU treatment. This patient did not have any apparent skin injury during the last three HIFU therapy and acquired satisfactory anti-tumor therapeutic effect. Conclusions: There are differences in the thermal selectivity of tumor tissues, which leads to different critical thermal injury temperature values that the tissue can tolerate. Ice-cooling can lower skin tissue temperature and reduce the thermal damage caused by HIFU treatment.